Pengaruh Gaya Kepemimpinan dan Komunikasi Terhadap Komitmen Anggota Karang Taruna - Ni Luh Sri Kasih; Kadek Mesya Apriliani Mesya (ARTHA SATYA DHARMA, 2023)
Abstract. The results of this study indicate that the influence of leadership style has an effect on commitment to Karang Taruna Bungkulan Village, this shows that leadership style has a positive and significant effect on commitment, in other words the leadership style applied to the Karang Taruna organization of Bungkulan village has an influence on the commitment of members youth organization. The effect of communication on commitment to Karang Taruna Bungkulan Village, this shows that communication has a positive and significant effect on commitment, in other words a good communication process and in accordance with the rules at work is able to increase the commitment of Karang Taruna members, with a communication process that goes well with all members Members also help members of the organization to be able to increase the commitment of its members. Based on the results of the calculations above, the f test obtained f-count> f-table, this indicates that leadership and communication styles have a joint effect on the commitment of youth to join as members of youth organizations.